SEMANTIC DESCRIPTION FOR THE TAXONOMY OF THE GEOSPATIAL SERVICES - Li, Hao; Wang, Yandong; Cheng, Penggen (Boletim de Ciências Geodésicas, 2015)
With the advances in the World Wide Web and Geographic Information System, geospatial services have progressively developed to provide geospatial data and processing functions online. In order to efficiently discover and manage the large amount of geospatial services, these services are registered with semantic descriptions and categorized into classes according to certain taxonomies. Most taxonomies for geospatial services are only provided in the human readable format. The lack of semantic description for taxonomies limits the semantic-based discovery of geospatial services. The objectives of this paper are proposing an approach to semantically describe the taxonomy of geospatial services and using the semantic descriptions for taxonomy to improve the discovery of geospatial services. A semantic description framework is introduced for geospatial service taxonomy to describe not only the hierarchical structure of classes but also the definitions for all classes. The semantic description of taxonomy base on this framework is further used to simplify the semantic description and registration of geospatial services and enhance the semantic-based service matching method.